An Analysis of Women Harassment in "Mad Max: Fury Road" Movie Using Feminism Theory by Simone de Beauvoir - Syavira Dewinta Chandra Wulan; Teguh Kasprabowo (Dinamika Bahasa dan Budaya, 2021)
Dewinta, Syavira. 2021. A Women Harassment in the Movie “Mad Max: Fury Road” Using Feminism Theory by Simone de Beauvoir : As a Feminist Study. A final project in a PatrialFilfillment of the requirements for a degree award of Sarjana Sastra in English Language and Literature.This study aimed to analyze women harassments in Mad Max Furry Road movie. The data was taken from the dialogs and the scenes in the movie that mostly displayed women harassment and how the main character struggled to fight back against those harassments. The method used in this study is qualitative method. The researcher analyze the data using the theory of Simon de Beauvoir namely feminism theory. The study answered three questions related to the kinds of harassments, the struggles of the main character and the impacts of the harassments. The result showed that there are some kinds of harassments. They are physical violence, sexual violence and Reproductive Coercion harassment. The study also showed how the main character stuggled by fight the oppression experienced by them that is to, namely by the female lead to save the other women, is by kidnapping them, use weapons and drive war cars and then fighting against the men who oppress them together with the other women. Lastly the study displayed the impacts of the harassments. They are feel traumatized and afraid if they meet men, they also live alone without men, they find it difficult to communicate with men again because they are worried that they will be bullied again.Keywords : Feminism, Masculinity, Women Harassment, Furiosa.